Interview with Gisele Girardi: in search of other cartographies in Brazilian education (PerCursos, 2025)
Born on the placid banks of the Ipiranga stream, in the city of São Paulo, in 1970, she entered the Geography course in 1987, at the University of São Paulo (USP). The choice for Geography was due to her girl's dream of being an archaeologist, a profession that meant being a scientist, discovering things and traveling. As there was no undergraduate course in Archeology at that time, Geography was one of the course options that would provide foundations for Archeology.During his undergraduate studies, his taste for mathematics and technical drawing turned Cartography into a field of interest. From then on, all internship experiences, working in the technical area (at the USP Cartography Laboratory and at the Geographic and Cartographic Institute of São Paulo), teaching at a higher level, in research - at undergraduate and postgraduate levels were with Cartography, making it possible to understand and problematize the technical dimensions of the discipline and search for foundations of a theoretical and methodological nature, from Geography, Cartography and other sciences with interfaces.Since 1998, she has been a professor of Cartography at the Federal University of Espírito Santo, working on Undergraduate and Postgraduate courses in Geography. Since 2020, she has been a full professor at the same university.